Family Satisfaction About Outcomes for Acute Liver Failure Patients with Fluid, Electrolyte, And Acid-Base Disturbances - Mohamed , Asmahan Serag; Mohammed, Mona Aly; Abdel-Malek, Mohamed Omar (International Journal of Membrane Science and Technology, 2023)
Background: Family satisfaction is considered an important indicator of outcomes in care. Good patient management leads to family satisfaction and significant improvement in acute liver failure patients' outcomes. Objective: To assess Family satisfaction about outcomes for acute liver failure patients with fluid, electrolyte, and acid base disturbances. Design: A descriptive research design was utilized to fulfill the aim of this study. Participants:-eighty family members for patients with acute liver failure. Method: Two tools were used to gather the data, the tool I acute liver failure patient assessment sheet, in which includes demographic data, hemodynamic and laboratory data. Tool II the patients' outcomes evaluation sheet and family satisfaction questionnaires used to assess Family satisfaction about outcomes for acute liver failure patients with fluid, electrolyte, and acid base disturbances. Results: The majority of families were satisfied with the management and outcomes of acute liver failure patients with fluid, electrolyte, and acid base disturbances. Conclusion: Families are satisfied with care, outcomes, and the information they received about their patients.